An investigation into parental perception of aspects of development and temperament in abused children - Carlin, Leslie Stanley (Department of Psychology, 2023)
This investigation focussed on child-related and parent-related characteristics in the area of child abuse. Specifically. developmental and temperament factors were stressed in non- CNS impaired abused children. Suggestions in the literature have pointed to the possible importance of studying temperament factors in these children. especially in the light of features in the developmental and medical histories which may place them at increased risk for abuse. Levels of development in abused children have been explored in other studies. but their findings with respect to the non-CNS impaired sub-group have not yielded clarity on their developmental status. The perceptions of the children's temperaments and levels of development by the mother was also investigated in the light of theoretical models of child abuse which have claimed that abusing parents place unrealistic demands on their children. who are not capable of complying. The performance of ten abused children was compared with normal controls (matched for age and sex and from the same social class) on the Grover Developmental Charts. The same two groups of children were observed in a free-play situation during which time their behaviour was rated on six categories of temperament. and in three areas of development. viz. gross-motor functioning. receptive language and socialization skills. Temperament categories and scoring methods for both parents and children were adapted for use in this research from the work of Alexander Thomas and his co-workers. Results suggested that the abused children performed at significantly lower levels in the areas of gross-motor functioning and language. Their performance in the language area was characterised by a tendency to fail in items having a "social" component. No significant differences were found in the other areas of development studied (socialization skills and cognitive development). However, these results suggested a trend towards lower levels of functioning which was in keeping with the significant findings in the gross-motor and language areas. The temperament comparisons did not yield significant findings. Analysis of the data obtained from mothers suggested that they tended to rate their children's language development significantly lower than controls. we're not significant. The other perceptual comparisons the findings are considered in the light of relevant theoretical models in the area of child abuse. Implications of the findings for future research, the limitations of the methodology employed, and the usefulness of the findings for clinical practice are discussed.